SOME OF THE PROBLEMS OF STIMULATION OF INNOVATIVE PROCESSES IN CONSTRUCTION MANAGEMENT - V. Bobylev (Вестник университета)
The article is devoted to topical issues of development of management of capital construction. Focuses on the stimulation of innovation processes, which is one of the basic and primary conditions of stable development of national economy and construction management. Special attention is paid to opportunities to enhance the innovation and receptivity to investing in the development of technologies that have become key priorities for the development of the national economy in conditions of globalization. After determining the importance of investing in innovation as a tool for economic development, noted that no investment project can do without a volume of completed construction works, i.e. the construction process accompanies the implementation of any innovation project. In these circumstances, special importance is regulatory support for the development of investments in innovation.